Sistemas agrários em Paraíba do Sul (1850-1920): um estudo de relações não-capitalistas de produção - Fragoso, João Luis Ribeiro (1983)
Study of the agrarian system that emerged from an export economy centered on one agricultural product. The coffee County of Paraiba do Sul on the Paraiba Valley (Rio de Janeiro) is taken as a case study for the period between 1850-1920. According to this purpose certain aspects concerned with the productive system have been giyen a privileged treatment such as: certain traits of its reproduction process and its relations of production. Along this dissertation, such traits have been associated with the concept of frequency of cultivation. On the other hand, through the analysis of such traits, especially the extensive character of the reproduction of the system as a whole, as well as the "association" of direct producers to ,the means of production, it is intended to demonstrate the logic of the agrarian system historically delimited and based on a given plantation economy. Finally, it is intended to demonstrate the persistency of that form of agricultural production, locally, along the post -slavery period. The fact that the agricultural regime based on free labor has been distinguished by its non-capitalist character results from the persistency of the above mentioned agrarian system as part of a defined form of agricultural production. The word "decadence" has been avoided as a definition of the period post-slavery. In fact, it is here suggested that the weathering (definhamento) of the agrarian system of the exportation economy, regionnally, was linked with its specific mechanisms of reproduction.